2023
DOI: 10.1007/s00467-023-06111-9
|View full text |Cite
|
Sign up to set email alerts
|

Should we consider sarcopenia in pediatric patients with chronic kidney disease? A preliminary cross-sectional analysis

Abstract: We investigated sarcopenia and its traits in children and adolescents with chronic kidney disease. MethodsPhysical function was assessed using handgrip strength (HGS) and the 60-second sit-to-stand (STS-60).Body composition was assessed by bioelectrical impedance and anthropometry through mid-upper arm circumference (MUAC). Probable sarcopenia was considered as low HGS, whereas sarcopenia by adding low MUAC. ResultsTwenty-two patients were evaluated (11 ± 4 years and 59% boys). Sarcopenia prevalence was 50%. L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In a single-center evaluation assessing grip strength and 60-s sit-to-stand test, >50% of children had low physical function via grip strength and 100% of children had low physical function per the sit-to-stand test. 92 The CKiD study reported reduced grip strength in their cohort with a median z score of -0.72 (IQR, −1.39 to 0.11). 93 The values from children with CKD stages 2-5 were significantly lower than those in children with CKD stage 1, and values were associated with CKD vintage, pubertal status, neuropsychiatric comorbidities, need for feeding support, alkali therapy, and hemoglobin levels.…”
Section: Kidney Transplantationmentioning
confidence: 94%
“…In a single-center evaluation assessing grip strength and 60-s sit-to-stand test, >50% of children had low physical function via grip strength and 100% of children had low physical function per the sit-to-stand test. 92 The CKiD study reported reduced grip strength in their cohort with a median z score of -0.72 (IQR, −1.39 to 0.11). 93 The values from children with CKD stages 2-5 were significantly lower than those in children with CKD stage 1, and values were associated with CKD vintage, pubertal status, neuropsychiatric comorbidities, need for feeding support, alkali therapy, and hemoglobin levels.…”
Section: Kidney Transplantationmentioning
confidence: 94%